2017
DOI: 10.1177/1062860617730900
|View full text |Cite
|
Sign up to set email alerts
|

Does Surveillance Bias Influence the Validity of Measures of Inpatient Complications? A Systematic Review

Abstract: Surveillance bias may threaten the accuracy of inpatient complication measures. A systematic literature review was conducted to examine whether surveillance bias influences the validity of selected Patient Safety Indicator- and health care associated infection-related measures. Ten venous thromboembolism (VTE) articles were identified: 7 trauma related, 3 postoperative, and 1 central line-associated bloodstream infection (CLABSI) article. Nine VTE articles found positive associations between deep vein thrombos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Based on retrospective life event interviews, this early work had no comparison group, and there was likely a detection (or surveillance) bias toward those with more difficulties. This is common in clinic-derived samples, but does raise threats to validity and issues of generalizability (Drake et al, 2017;Chen et al, 2018). These must be considered in data interpretation for both earlier and more recent clinic-based studies.…”
Section: E Arlier Data On S Econdary D Isab Ilitie S In Fa S Dmentioning
confidence: 99%
“…Based on retrospective life event interviews, this early work had no comparison group, and there was likely a detection (or surveillance) bias toward those with more difficulties. This is common in clinic-derived samples, but does raise threats to validity and issues of generalizability (Drake et al, 2017;Chen et al, 2018). These must be considered in data interpretation for both earlier and more recent clinic-based studies.…”
Section: E Arlier Data On S Econdary D Isab Ilitie S In Fa S Dmentioning
confidence: 99%
“…A systematic review of surveillance bias in outcome measures concluded that this issue particularly affects venous thromboembolism (VTE) diagnosis. They found that six trauma-related and two post-operative VTE studies reported evidence of surveillance bias [ 16 ]. Previous work on VTE reported a paradoxical relationship between VTE and outcome measures similar to what we found in our analysis - high-quality centers had higher rates of VTE than low-quality centers [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,[14][15][16] Although standardized comparative metrics facilitate comparison among peer groups, review of the literature suggests that gaps remain about their actionability due to the lack of specificity and detail needed to allow hospital leaders to understand specific areas of high and low performance and target quality improvement efforts accordingly. 14,15,[17][18][19][20][21] Consider as an example PSI 04, the death rate among surgical inpatients with serious treatable complications. 7,22 This metric is largely recognized as the measure of a health care institution's "failure to rescue" (FTR) performance and is a critical patient safety measure, as it is associated with a 2.5-fold variation in highest-versus lowest-quintile hospital mortality rates.…”
mentioning
confidence: 99%
“…Large-scale adoption of PSIs and IQIs has produced extensive amounts of hospital-specific and comparative performance data and allowed for critical review of validity 10,14–16 . Although standardized comparative metrics facilitate comparison among peer groups, review of the literature suggests that gaps remain about their actionability due to the lack of specificity and detail needed to allow hospital leaders to understand specific areas of high and low performance and target quality improvement efforts accordingly 14,15,17–21 …”
mentioning
confidence: 99%